Study of Biodiversity of Algae and Cyanobacteria of Mutnovsky and Gorely Volcanoes Soils (Kamchatka Peninsula) Using a Polyphasic Approach - Rezeda Z. Allaguvatova; Arthur Yu. Nikulin; Vyacheslav Yu. Nikulin; Veronika B. Bagmet; Lira A. Gaysina (Diversity, 2022)
Volcanic activity has a significant influence on the development of terrestrial ecosystems, including the Kamchatka Peninsula. We aimed to study the terrestrial algoflora of the Mutnovsky and Gorely volcanoes based on the use of clonal cultures of algae and cyanobacteria, and phenotypic and molecular genetic analyses. A total of 48 taxa were identified: 9 cyanobacteria, 32 Chlorophyta (11 Chlorophyceae, 21 Trebouxiophyceae), 3 Ochrophyta, and 4 Charophyta. In soils of the Mutnovsky volcano, 30 taxa were found, and in soils of the Gorely volcano, 24 were observed. In the studied area, small coccoid or mucilage-producing algae, which belong to cosmopolitan species, were identified, including representatives of the genera Bracteacoccus, Chlorococcum, Coccomyxa, Coelastrella, Klebsormidium, Neocystis, and Vischeria. Certain taxa were detected for the first time in the studied region, including Bracteacoccus bullatus, Chlorococcum hypnosporum, Chlorococcum lobatum, Coccomyxa subellipsoidea, Klebsormidium nitens, Leptosira obovata, Lobosphaera incisa, Parietochloris pseudoalveolaris, Stenomitos tremulus, and Vischeria magna. Our analysis of the algal communities at different altitudes reveals expansion in species richness with increasing distance from the tops of the volcanoes. The obtained data allowed us to estimate the real biodiversity of terrestrial algae and cyanobacteria of Kamchatkan volcanic soils, as well as the ecologies of these microorganisms.